2003
DOI: 10.1007/s00707-002-0985-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nonuniform temperature gradients on the onset of oscillatory Marangoni convection in a magnetic field

Abstract: This article theoretically studies the onset of oscillatory Marangoni convection in a horizontal layer of an electrically conducting fluid, to which a nonuniform thermal gradient and a uniform magnetic field are applied. The top surface of a fluid layer is deformably free and the bottom is rigid. By means of the linear stability theory and a normal mode analysis, the eigenvalue equations of the perturbed state are solved by using the fourth-order Runge-Kutta-Gill's method with the shooting technique. The compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The surface tension on the free interface is a linear function of temperature and it decreases linearly with the temperature increasing. The basic governing equations for the half-floating zone thermocapillary convection include the mass, momentum, and energy conservation equations [6][7] [8]. Basic non-dimensional governing equations are given as following:…”
Section: Controlling Equationsmentioning
confidence: 99%
“…The surface tension on the free interface is a linear function of temperature and it decreases linearly with the temperature increasing. The basic governing equations for the half-floating zone thermocapillary convection include the mass, momentum, and energy conservation equations [6][7] [8]. Basic non-dimensional governing equations are given as following:…”
Section: Controlling Equationsmentioning
confidence: 99%
“…Takashima, M [3] presented a detailed numerical study of the linear stability analysis of Benard-Marangoni convection, including stationary and oscillatory modes, and focused the influence of the Crispation number on the conditions for a competition between two of these kinds of modes. Char and Chiang [4] examined the boundary effects on the Benard-Marangoni instability problem in the presence of an electric field, and found that the boundary effects of the solid plate have great influences on the stability of the system. Recently, Hashim and Wilson [5] advanced the analyses of [3,4] to the BenardMarangoni instability of a horizontal liquid layer in the most physically-relevant case when Rayleigh number and Marangoni number are linearly dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Char and Chiang [4] examined the boundary effects on the Benard-Marangoni instability problem in the presence of an electric field, and found that the boundary effects of the solid plate have great influences on the stability of the system. Recently, Hashim and Wilson [5] advanced the analyses of [3,4] to the BenardMarangoni instability of a horizontal liquid layer in the most physically-relevant case when Rayleigh number and Marangoni number are linearly dependent. All these previous investigators are restricted to the convective system in the absence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that in addition to an increase in Marangoni number, the unsteadiness also increases with the increase in the concentration of the imposed heat flux. Char and Chen (2003) studied the effect of non‐uniform temperature gradients at the onset of oscillatory Marangoni convection in a perpendicularly applied magnetic field. Since the Lorentz force suppresses the Marangoni convection, they established the result that the critical Marangoni number increases with the increase in the strength of magnetic field, and Prandtl number.…”
Section: Introductionmentioning
confidence: 99%